Comparative efficacy and tolerability of three treatments in old people with osteoporotic vertebral compression fracture: a network meta-analysis and systematic review. - Ling-Xiao Chen; Yu-Lin Li; Guang-Zhi Ning; Yan Li; Qiu-Li Wu; Jin-Xiu Guo; Hong-Yu Shi; Xiao-Bo Wang; Yong Zhou; Shi-Qing Feng (PLoS ONE)
Purpose The question which kind of methods is most suitable for treating the old people for osteoporotic vertebral compression fracture is still discussed and pairwise meta-analyses cannot get hierarchies of these treatments. Our aim is to integrate the evidence to provide hierarchies of the comparative efficacy measured by the change of VAS (Visual Analogue Scale) and tolerability measured by incidence of new fractures and risk of all-cause discontinuation on three treatments (percutaneous vertebroplasty (PVP)、balloon kyphoplasty (BK) and conservative treatment (CT)). Methods We performed a Bayesian-framework network meta-analysis of randomized controlled trials (RCTs) to compare three treatments for the old people with osteoporotic vertebral compression fracture. The eligible RCTs were identified by searching Amed, British Nursing Index, Embase, Pubmed, the Cochrane Central Register of Controlled Trials (CENTRAL), Google scholar, SIGLE, the National Technical Information Service, the National Research Register (UK) and the Current Controlled Trials databases. Data from three outcomes (e.g. VAS, risk of all-cause discontinuation and incidence of new fractures) were independently extracted by two authors. Results A total of five RCTs were finally included into this article. PVP and BK significantly decreased VAS when compared with CT. BK had a significantly lower risk of all-cause discontinuation contrast to CT. Three treatments (BK, PVP and CT) had no significant differences in the incidence of new fractures. Conclusions PVP may be the best way to relieve pain, CT might lead to the lowest incidence of new fractures and BK might had the lowest risk of all-cause discontinuation in old people with osteoporotic vertebral compression fracture. More large-scale and longer duration of follow-up studies are needed.